Impact of Transformational Leadership on Employee Engagement - Devi, Saloni; Mahajans, Rachna (International Journal of Psychosocial Rehabilitation, 2019)
Transformational leadership is a form of leadership in which relationship are planned around a combines reason in a way that over, inspire and increase the performance and moral aspiration of supporters. The proposed study examines the impact of transformational leadership on employee engagement. Data was collected from the one of the leading private bank i.e. Jammu and Kashmir Bank Pvt. Ltd. (J&K bank) employees in Jammu and Kashmir and convenience sampling method was used to collect the data. A 5 point likert scale questionnaire, consisting of 27 items was designed. Hypotheses were tested by using structural equation modelling (SEM). The research findings revealed that transformational leadership have positive and significant impact on employee engagement.